“El lugar de una mujer está en la tecnología”: un análisis de perfiles brasileños de Instagram sobre mujeres en tecnología - Gonçalves, Marina Borges (2023)
The disparity in the number of women and men working in STEM fields is a widespread issue among researchers around the world; however, given its complexity, there are always elements to be reflected on and problematized. With this in mind, this paper presents a study that aimed to analyze, based on the precepts of Pêcheux’s discourse analysis, Brazilian Instagram profiles about women in technology, based on a survey carried out by the ELLAS network. A total of 63 profiles were found, and of these, 18 individual profiles were chosen for analysis, in which it was possible to verify the focus on teaching how to enter and progress in this area.